Analysis of Stress Levels in Adolescents at Ciamis Senior High School 2 - Idhfi Marpatmawati; Heri Budiawan; Wawan Rismawan; Nandita Milda Hidayat (HealthCare Nursing Journal, 2025)
Adolescents are an age group particularly vulnerable to stress due to academic, social, and emotional pressures. Unmanaged stress can negatively affect mental health and academic performance. This study aims to analyze stress levels among adolescents at Ciamis Senior High School 2 based on age and gender. A descriptive quantitative approach was used with purposive sampling. The research instrument was the DASS questionnaire, distributed to 861 respondents aged 14–18 years. Data were analyzed using descriptive statistical methods. The majority of respondents experienced moderate (33.57%), severe (22.42%), and extremely severe (16.61%) levels of stress. Adolescents aged 16–17 and females showed higher stress levels than other groups. The findings indicate that mid-adolescents and females are more prone to psychological pressure. This is consistent with Erikson's psychosocial development theory and the transactional stress model by Lazarus & Folkman. Most adolescents experience moderate to extremely severe stress, particularly those aged 16–17 and females. Contextual and gender-sensitive mental health interventions are needed in the school environment